Personal Knowledge and Faith of a Scientist: Providence, Gratefulness, Sense of Vocation Sickness and Medicine, Education and the Belief in God and Mathematics - KOVÁCS, Ábrahám (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2025)
This study intends to probe into the Christian faith of a well-known Hungarian scientist, István Hatvani (1718–1786). It does not claim to look at all of his writings by scrutinizing all of his statements about how science and Christian faith encountered in his life. However, it seeks to analyse his autobiography with a view to understanding how his personal life story, a lived Christian faith, had informed and influenced the perception of his own pursuit of science by the time he began to teach at one of the most prestigious Protestant centres of knowledge in Central Europe, at the Debrecen Reformed College in Hungary. The “confession” and reflection, as will be seen, is really informative about the basis of his faith and intention. This research paper focuses on three aspects typical of Calvinism such as providence, gratefulness, a call for vocation, a mandate and arrives at the beautiful confession of a scientist about God the Sustainer and Provider of all living creatures.